2024
DOI: 10.3847/1538-3881/ad26f0
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Point Masses. II. Non-Keplerian Shape Effects Are Detectable in Several TNO Binaries

Benjamin C. N. Proudfoot,
Darin A. Ragozzine,
Meagan L. Thatcher
et al.

Abstract: About 40 trans-Neptunian binaries (TNBs) have fully determined orbits with about 10 others being solved except for breaking the mirror ambiguity. Despite decades of study, almost all TNBs have only ever been analyzed with a model that assumes perfect Keplerian motion (e.g., two point masses). In reality, all TNB systems are non-Keplerian due to nonspherical shapes, possible presence of undetected system components, and/or solar perturbations. In this work, we focus on identifying candidates for detectable non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Based on our fits, we can roughly estimate that ∼2-4 new epochs of observations in the mid-2020s (or beyond) are necessary to constrain Haumea's J 2 with ∼10% precision. Past work has shown that timing observations at certain, well-selected times can substantially improve the quality of the resulting orbit fits (Proudfoot et al 2024). These times occur when the uncertainties in cos a d D and Δδ in Table 3 are at (local) maximum.…”
Section: Future and Past Observationsmentioning
confidence: 99%
“…Based on our fits, we can roughly estimate that ∼2-4 new epochs of observations in the mid-2020s (or beyond) are necessary to constrain Haumea's J 2 with ∼10% precision. Past work has shown that timing observations at certain, well-selected times can substantially improve the quality of the resulting orbit fits (Proudfoot et al 2024). These times occur when the uncertainties in cos a d D and Δδ in Table 3 are at (local) maximum.…”
Section: Future and Past Observationsmentioning
confidence: 99%